COMPARISON OF ATTITUDES OF GENERAL DENTIST VS PAEDIATRIC DENTISTS TOWARDS PAIN MANAGEMENT IN CHILDREN AND ADOLESCENTS IN PAKISTAN - Bangash, Madeeha; Mustafa, Laila; Mansur, Aamna; Rashid, Sahd; Irshad, Muhammad; Junaid, Syed Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To access whether there was a difference of attitude between general dentists and specialist Paediatric dentists regarding management of pain.Study Design: Questionnaire based survey.Place and Duration of Study: This survey was performed among general and Peadiatric dentists working in various setups in Pakistan, from Jun 2019 to Nov 2019.Methodology: This survey was performed among actively partaking general dentists and specialist Paediatric dentists (n=345) working in various hospital setups in Pakistan over a period of 6 months. They were asked to fill questionnaire about pain management with various clinical scenarios, the type of pharmaceutical agent used and the timing of pre-operative analgesics, as well as the use of topical anesthesia and use of local anesthetic. The questionnaire also contained socio-demographic profiles of the dentists participating in the survey. Those who were retired and above 70 years of age were excluded from the study.Results: Out of 345 participants only 287 responded with a relatively higher response rate among specialist Paediatric dentists as compared to general dentists. Forty were dropouts. However, the response rates between gender did not show any significant difference. The mean age of general dentists was 39.49 (SD: 11.68) whereas, mean age for specialist Paediatric dentists was 41.19 (SD: 10.8). About 161 (59.4%) of the general dentists and 16 (100%) specialist Paediatric dentists recommended pre/post op analgesics (p=0.000). Ibuprofen was the most commonly recommended pre-op analgesic in Pakistan (p=0.005) recommended by about 108 (39.85%) general dentists and 11 (68.75%) Paediatric dentists. About 58 (21.4%) general dentists recommended pre-op analgesicsmore than an hour before treatment (p=0.008) and 5 (31.25%) specialist Paediatric dentists recommended it about an hour before treatment.Conclusion: Specialist Paediatric dentists were found using all kinds of pain reducing strategies, topical and local anesthesia more frequently while treating primary teeth as compared to general dentists.